An empirical analysis of double reduction education policy based on public psychology - Zhang, Xin; Zhao, Weibin; Zhou, Kai (Frontiers in Psychology, 2022)
To effectively reduce the homework burden and off-campus training burden of students in the compulsory education stage in China, China adopts the double reduction policy to carry out corresponding governance in the field of education. This study aims to explore the public's psychological cognition of the current education system under the implementation of the double reduction policy. The public's opinion data on education concepts under the implementation of the double reduction policy are collected, then the SPSS software and Amos software to quantitatively analyze the public's educational concept data are used, and a corresponding structural model equation to analyze the public's opinion on the implementation of the double reduction policy is established. The psychological concepts of all aspects of education are observed, the public's psychological views on education under the implementation of the double reduction policy are finally obtained, the ideological connotation of popularizing the double reduction policy for the general public is provided, and the balanced development of the domestic education system for the implementation of the double reduction policy is ensured. Two suggestions are made in order to provide a corresponding reference for the public's psychological cognition research on the current education system under the implementation of the double reduction policy.